2012
DOI: 10.1007/s00271-012-0383-8
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the effects of saline water use in wheat-cultivated lands using the UNSATCHEM model

Abstract: Waters of poor quality are often used to irrigate crops in arid and semiarid regions, including the Fars Province of southwest Iran. The UNSATCHEM model was first calibrated and validated using field data that were collected to evaluate the use of saline water for the wheat crop. The calibrated and validated model was then employed to study different aspects of the salinization process and the impact of rainfall. The effects of irrigation water quality on the salinization process were evaluated using model sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 39 publications
1
35
0
Order By: Relevance
“…No significant increase in soil salinity was observed under fresh water application. Rasouli et al (2013) evaluated the effects of saline water irrigation in wheat-cultivated lands in Iran. The study revealed that rainfall distribution played a key role in creation of soil salinity profile during the growing season, and off-season winter rainfall was more effective in salt leaching than a similar amount of rainfall distributed throughout winter, spring, and autumn seasons.…”
Section: Introductionmentioning
confidence: 99%
“…No significant increase in soil salinity was observed under fresh water application. Rasouli et al (2013) evaluated the effects of saline water irrigation in wheat-cultivated lands in Iran. The study revealed that rainfall distribution played a key role in creation of soil salinity profile during the growing season, and off-season winter rainfall was more effective in salt leaching than a similar amount of rainfall distributed throughout winter, spring, and autumn seasons.…”
Section: Introductionmentioning
confidence: 99%
“…is attributed to significant leaching of Ca 2+ and Mg 2+ from the surface layer and continuous desorption of exchangeable Na + . Rasouli et al (2013) used model UNSATCHEM to predict EC sw in a field experiment with winter wheat and varying irrigation water salinities. They obtained RMSE values that ranged from 0.52 to 1.01 dSm -1 and from 1.60 to 2.13 dSm -1 for the validation period, with irrigation water salinities of 6.5 and 11.5 dSm -1 , respectively.…”
Section: Overall Salinity and Sodicitymentioning
confidence: 99%
“…Adoption of suitable salinity control measures requires determination of salt and water movement through the soil profile and prediction of crop response to soil water and soil salinity, subject to various climatic, soil and agronomic factors (Rasouli et al, 2013). Mathematical models that consider and integrate various climatic, crop, and edaphic factors have been suggested as useful tools for assessing the best management practices for saline conditions (Gonçalves et al, 2006;Ramos et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The flow to individual roots is ignored and the overall root system is assumed to extract water from each point of the root zone. While the complete insight into the physical process of root water uptake was not required and therefore the determination of soil and plant parameters were more empirical (Feddes, 1988;Zhuang et al, 2001, Lekakis et al, 2011;Rasouli et al, 2013).…”
Section: Introductionmentioning
confidence: 99%